2021
DOI: 10.3390/app11125718
|View full text |Cite
|
Sign up to set email alerts
|

Neuronutraceuticals Modulate Lipopolysaccharide- or Amyloid-β 1-42 Peptide-Induced Transglutaminase 2 Overexpression as a Marker of Neuroinflammation in Mouse Microglial Cells

Abstract: Background: Tissue type 2 transglutaminase (TG2, E.C. 2.3.2,13) is reported to be involved in the phagocytosis of apoptotic cells in mouse microglial BV2 cells and peripheral macrophages. In this study, by using lipopolysaccharide (LPS)- or amyloid-β 1-42 (Aβ 1-42) peptide-stimulated microglial cell line BV2 and mouse primary microglial cells, we examined the effects of different neuronutraceutical compounds, such as curcumin (Cu) and N-Palmitoylethanolamine (PEA), known for their anti-inflammatory activity, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Also, PEA was found to exert protective properties in wild-type mouse cell cultures but not in AD mouse neuronal cultured cells overexpressing Aβ, suggesting its effectiveness in early AD or when Aβ is accumulating and initiating damage in the central nervous system ( 35 ). Similar findings were found among AD models where in vitro PEA application reduced neuroinflammation ( 52 ) and astrogliosis ( 38 , 45 ), supporting neuronal viability and survival ( 38 , 45 ), and also improving enteric inflammation ( 50 ).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Also, PEA was found to exert protective properties in wild-type mouse cell cultures but not in AD mouse neuronal cultured cells overexpressing Aβ, suggesting its effectiveness in early AD or when Aβ is accumulating and initiating damage in the central nervous system ( 35 ). Similar findings were found among AD models where in vitro PEA application reduced neuroinflammation ( 52 ) and astrogliosis ( 38 , 45 ), supporting neuronal viability and survival ( 38 , 45 ), and also improving enteric inflammation ( 50 ).…”
Section: Resultssupporting
confidence: 79%
“…To confirm the results obtained with the in vitro models, some studies made the same PEA treatment ex vivo (Tables 1B, 2B) with organotypic cultures challenged with Aβ (22, 32, 33) or lipopolysaccharide (LPS) (52). Converging evidence suggests that PEA may enhance neuroprotection against the neurodegenerative processes associated with Aβ deposition, including astrocyte activation (32, 33) and neuroinflammation (32, 33, 52).…”
Section: Ex Vivo Pea Exposure In In Aβ Exposed Animal Cells and Ad An...mentioning
confidence: 78%
See 2 more Smart Citations
“…Several findings demonstrated that CUR shows strong neuro-protective effects improving cognitive function; promoting axonal regeneration [ 23 , 24 , 25 , 26 , 27 , 28 ]; reducing apoptotic proteins; upregulating the anti-apoptotic protein Bcl-2; and also stimulating neurogenesis and neuroplasticity. In addition, recent data demonstrated that CUR is able to downregulate TG2 overexpression in mouse microglial cells (exposed to lipopolysaccharide or Aβ 1–42 full peptide), thus suggesting its possible use for neuroprotection in neuroinflammatory pathologies, including AD [ 29 ]. In vitro and in vivo studies on AD models also demonstrated that CUR was able to inhibit the formation of Aβ oligomers [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%